Petrogenesis, Magma Source, and Geodynamics of Paleogene Mafic Rocks, Huimin Sag, Jiyang Depression, Eastern China - Lihua Gao; Zhigang Song; Chao Han; Mei Han; Chenlin Zhu; Di Xia; Zuozhen Han; Shuangjian Li (Geofluids)
A suite of Paleogene mafic rocks was collected from boreholes in the Huimin Sag of the Jiyang Depression with the aim of investigating the petrogenesis and nature of mantle source for these rocks and further providing insights into the characteristic of related mantle plume. Whole-rock geochemical data indicate that the mafic rocks have relatively lower SiO2 (42.93%–48.57%) contents and similar characteristics to alkaline basalt and belong to transitional calc-alkaline series. These samples were clearly enriched in LREEs and depleted in HREEs and were also characterized by the enrichment of LILEs, incompatible elements, and HFSEs, similar to those of the Ocean Island Basalt (OIB). In addition, they exhibited Pb enrichment; Y, Pr, and Yb depletion; absence of Nb-Ta anomalies; high Hf and low Zr; and Rb/Yb ratios exceeding 1.0, indicating characteristics of intraplate rift-type alkaline basalt. The samples exhibited (Th/Ta)PM and (La/Nb)PM ratios less than 1 and plotted within the OIB, EMI, and EMII fields, indicating that crustal components had no role in the generation of the rocks. With the exception of individual samples that have a distinctive range of εNd values, the majority of samples have complex εNd values of -1.15 to 5.56, indicating a mixture of different sources, which was also apparent in the δ18O-87Sr/86Sr diagram, in which the samples plot close to the downward nonlinear curve. Based on the isotopic and trace elemental analyses, these igneous rocks are intraplate rift-type alkaline basalt and are of mantle plume origin. The variations in 87Sr/86Sr, 143Nd/144Nd, εNd values, LREEs, and HFSEs were probably due to the different locations of the mantle plume for different samples. The primary magma of the rocks likely originated from the melting of a mantle plume and the further metasomatism of lithospheric mantle, continental, or oceanic crust.